Edpidemiology, Clinical Profile and Short- Term Outcome of Hypertensive Crisis in N'Djamena (Chad) - Dangwe Temoua, Naibé; Dallah Tchimby Urbain, Houba; Abdelmadjid Zacharia, Zakaria; Ndarwadjigue Estelle, Djangde; Koboy Allah Amine, Adjougoulta; Lucien, Allawaye; Ali Ahmat, Adam; Oumar, Mahamat-Azaki; Dikoua, Binwe; Narcisse, Douné; Mianrho Hiby, Langtar; Nahodjide, Djimadoum; et al. (Journal of Hypertension and Cardiology, 2024)
Objective Hypertensive crisis is an increasingly frequent medical condition in our context. Its management in medical emergencies is a real challenge for physicians. Few data on hypertensive crisis are available in Chad. The aim of this study was to investigate the epidemiological, clinical and prognostic characteristics of hypertensive crisis in the medical emergency department of Reference National Teaching Hospital in N'Djamena. Patient and methods This was a prospective cohort study running from 1er March 2020 to October 31 2020. Patients presenting with a sudden and severe rise in blood pressure (systolic ≥ 180 mmHg and/or diastolic ≥ 110 mmHg) with or without acute target-organs damage, had been consecutively included and followed up over a period of one (01) month. Epidemic and clinical characteristics on admission, and morbidity and mortality parameters during the course of the disease were collected. The Kaplan-Meier method and the Cox model were used to analyze survival and factors associated with death, with a significance level of p<0.05. Results Of the 3978 hypertensive patients admitted to medical emergencies, 252 had a hypertensive crisis, i.e. a prevalence of 6.3%. Two hundred and seventeen (217) patients were included in the study, divided into 149 cases (69%) of hypertensive emergency and 67 cases (31%) of hypertensive hypertensive urgencies. The mean age of the patients was 55.2 ± 14 years (20 and 80 years) and 67% were male. Hypertension was known in 138 patients (64%). At least one complication was present on admission in 69% of patients. Complications were classified as cardiac (50.7%), neurological (38.2%), kidney impairment (46.5%) and ocular (46.1%). The average number of antihypertensive drugs used was 2 ± 0.83 14. Calcium antagonists (86.5%), diuretics (35.5%), converting enzyme inhibitors or angiotensin II receptor antagonists (33.3%) and betablockers (18%) were the pharmacological classes prescribed. Good compliance during follow-up was observed in 124 patients. One-month survival was 84% for all patients, with a 16% mortality rate. Factors associated with death were the duration of hypertension, and the occurrence of cardiovascular, renal dysfunction and ocular disease (p < 0.05). Conclusion Hypertensive crisis is a frequent pathology in sub-Saharan Africa, with high morbidity and mortality. Prevention requires early detection and effective management of hypertension.
Keywords: Hypertensive crisis; Morbidity; Mortality; N’Djamena; Chad